2011
DOI: 10.1111/j.1365-2109.2011.02955.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity in microalgae cultures

Abstract: Five cultures of microalgae (Chlorella minutissima, Tetraselmis chui, Nannochloropsis sp., Arthrospira platensis and Isochrysis sp.) with no culturable bacteria were tested for their ability to inhibit the growth of six Vibrio bacterial strains (V. parahaemolyticus, V. anguillarum, V. splendidus, V. scophthalmi, V. alginolyticus and V. lentus). The influence of light on the antibacterial activity of the microalgae was investigated. All microalgae cultures inhibited the growth of bacteria compared with the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(55 citation statements)
references
References 29 publications
4
50
0
1
Order By: Relevance
“…Chlorella species have high antimicrobial activity (Ördög et al 2004;Ghasemi et al 2007;Kokou et al 2012) as was found in the present study where noteworthy MIC (<1 mg mL −1 ) values were recorded in about 80 % of the tested extracts. While studies evaluating the potential of different type of microalgae are well documented (Ördög et al 2004;Bhagavathy et al 2011;Nair and Krishika 2011;Prakash et al 2011;Kokou et al 2012), attempts to manipulate the antimicrobial activity based on the culture conditions are limited (Noaman et al 2004;Abedin and Taha 2008;Aremu et al 2014). The current study highlights the potential of manipulating the N concentration and cultivation time to increase the antimicrobial activity of three Chlorella strains as antimicrobial activity generally varied over time relative to the N content in the cultures.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Chlorella species have high antimicrobial activity (Ördög et al 2004;Ghasemi et al 2007;Kokou et al 2012) as was found in the present study where noteworthy MIC (<1 mg mL −1 ) values were recorded in about 80 % of the tested extracts. While studies evaluating the potential of different type of microalgae are well documented (Ördög et al 2004;Bhagavathy et al 2011;Nair and Krishika 2011;Prakash et al 2011;Kokou et al 2012), attempts to manipulate the antimicrobial activity based on the culture conditions are limited (Noaman et al 2004;Abedin and Taha 2008;Aremu et al 2014). The current study highlights the potential of manipulating the N concentration and cultivation time to increase the antimicrobial activity of three Chlorella strains as antimicrobial activity generally varied over time relative to the N content in the cultures.…”
Section: Discussionsupporting
confidence: 63%
“…Furthermore, the effect of different stress factors on some biochemical changes in semi-continuous batch cultures of Chlorella minutissima grown in nitrogen (N)-deficient conditions have been highlighted (Ördög et al 2012). Even though the pharmacological potential of Chlorella has been well-documented (Amaro et al 2011;Kokou et al 2012;Shanab et al 2012), there is no evidence of how the manipulation of the growth conditions influence the phytochemical and biological activities. Hence, the current study focused on the effect of N concentration and culture age (5 and 10 days in culture) on the phytochemical (phenolic, flavonoid, condensed tannin, and iridoid) content and pharmacological (antioxidant, acetylcholinesterase inhibitory [AChEI], and antimicrobial) activities of three Chlorella strains.…”
Section: Introductionmentioning
confidence: 96%
“…A study reports that when green water-shrimp growout method was applied, outbreak of luminous vibriosis could be prevented in tiger shrimp culture ponds (Rosa, 2004;Corre et al, 2005;Jimenez et al, 2016). The mechanism behind the beneficial effect of green water includes the algal production of antibacterial substances as well as production of compounds that inhibit virulence gene regulation for e.g., quorum sensing inhibitors (Natrah et al, 2011;Kokou et al, 2012). Therefore, it is evident that the green water had the ability to control harmful Vibrio population in the pond and this can be attributed as a reason for the enhanced survival rate recorded in treatment ponds.…”
Section: Discussionmentioning
confidence: 92%
“…Several mechanisms have been linked to the beneficial effect of green water, including the production of antibacterial substances by algae (Kokou et al, 2012) and compounds that inhibit virulence gene (Natrah et al, 2011;. Considering the significance of green water, a study was conducted to test the efficacy of green water from a fish culture pond on the growth, health status and production of Pacific white shrimp, Penaeus vannamei (Boone, 1931) an ideal candidate species for coastal aquaculture.…”
Section: Introductionmentioning
confidence: 99%
“…There is ample experimental evidence of its antitumor, anticoagulant, antibacterial, antioxidant, and antihyperlipidemia effects in addition to a hepatoprotective property and the immune-stimulatory activity of enzymatic protein hydrolyzate [30][31][32][33][34]. Many antioxidant compounds are thought to be responsible for Chlorella functional activities.…”
Section: Types Of Bioactive Compoundsmentioning
confidence: 99%